Vocal differentiation parallels development of auditory saccular sensitivity in a highly soniferous fish - Vasconcelos, Raquel O.; Alderks, Peter W.; Ramos, Andreia; Fonseca, Paulo J.; Amorim, M. Clara P.; Sisneros, Joseph A. (Journal of Experimental Biology, 2015)
Vocal differentiation is widely documented in birds and mammals but has been poorly investigated in other vertebrates, including fish, which represent the oldest extant vertebrate group. Neural circuitry controlling vocal behaviour is thought to have evolved from conserved brain areas that originated in fish, making this taxon key to understanding the evolution and development of the vertebrate vocal-auditory systems. This study examines ontogenetic changes in the vocal repertoire and whether vocal differentiation parallels auditory development in the Lusitanian toadfish Halobatrachus didactylus (Batrachoididae). This species exhibits a complex acoustic repertoire and is vocally active during early development. Vocalisations were recorded during social interactions for four size groups (fry: <2 cm; small juveniles: 2–4 cm; large juveniles: 5–7 cm; adults >25 cm, standard length). Auditory sensitivity of juveniles and adults was determined based on evoked potentials recorded from the inner ear saccule in response to pure tones of 75–945 Hz. We show an ontogenetic increment in the vocal repertoire from simple broadband-pulsed ‘grunts’ that later differentiate into four distinct vocalisations, including low-frequency amplitude-modulated ‘boatwhistles’. Whereas fry emitted mostly single grunts, large juveniles exhibited vocalisations similar to the adult vocal repertoire. Saccular sensitivity revealed a three-fold enhancement at most frequencies tested from small to large juveniles; however, large juveniles were similar in sensitivity to adults. We provide the first clear evidence of ontogenetic vocal differentiation in fish, as previously described for higher vertebrates. Our results suggest a parallel development between the vocal motor pathway and the peripheral auditory system for acoustic social communication in fish.

Ontogenetic development of the inner ear saccule and utricle in the Lusitanian toadfish: Potential implications for auditory sensitivity - Chaves, Patrícia P.; Valdoria, Ciara M. C.; Amorim, M. Clara P.; Vasconcelos, Raquel O. (Hearing Research, 2017)
Studies addressing structure-function relationships of the fish auditory system during development are sparse compared to other taxa. The Batrachoididae has become an important group to investigate mechanisms of auditory plasticity and evolution of auditory-vocal systems. A recent study reported ontogenetic improvements in the inner ear saccule sensitivity of the Lusitanian toadfish, Halobatrachus didactylus, but whether this results from changes in the sensory morphology remains unknown. We investigated how the macula and organization of auditory receptors in the saccule and utricle change during growth in this species. Inner ear sensory epithelia were removed from the end organs of previously PFA-fixed specimens, from non-vocal posthatch fry (<1.4 cm, standard length) to adults (>23 cm). Epithelia were phalloidin-stained and analysed for area, shape, number and orientation patterns of hair cells (HC), and number and size of saccular supporting cells (SC). Saccular macula area expanded 41x in total, and significantly more (relative to body length) among vocal juveniles (2.3–2.9 cm). Saccular HC number increased 25x but HC density decreased, suggesting that HC addition is slower relative to epithelial growth. While SC density decreased, SC apical area increased, contributing to the epithelial expansion. The utricule revealed increased HC density (striolar region) and less epithelial expansion (5x) with growth, contrasting with the saccule that may have a different developmental pattern due to its larger size and main auditory functions. Both macula shape and HC orientation patterns were already established in the posthatch fry and retained throughout growth in both end organs. We suggest that previously reported ontogenetic improvements in saccular sensitivity might be associated with changes in HC number (not density), size and/or molecular mechanisms controlling HC sensitivity. This is one of the first studies investigating the ontogenetic development of the saccule and utricle in a vocal fish and how it potentially relates to auditory enhancement for acoustic communication.
Keywords: Auditory sensitivity; Batrachoididae; Hair cell; Ontogeny; Saccule; Utricle

Fish Sounds and Mate Choice - Amorim, M. Clara P.; Vasconcelos, Raquel O.; Fonseca, Paulo J. (Sound Communication in Fishes, 2015)
Fish acoustic signals associated with mating behaviour are typically low-frequency sounds produced by males when in close proximity to females. However, some species make sounds that serve the function and follow the design of advertisement calls, well known in insects, anurans, and birds. Close-range courtship acoustic signals may be used by females in mate assessment as they contain information of male quality such as size and condition. For example, sound-dominant frequency, amplitude, and fatigue resistance may signal body size whereas pulse period (i.e. muscle contraction rate) and calling activity are related with body condition in some species. Some signal features, such as sound pulse number, may carry multiple messages including size and condition. Playback experiments on mate choice of a restricted number of species suggest that females prefer vocal to silent males and may use sound frequency, amplitude, and mainly calling rateCalling ratewhen assessing males. The assessment of males by females becomes more challenging when males engage in choruses or when sounds are otherwise masked by anthropogenic noise but almost nothing is known about how these aspects affect mating decisions and fish reproductive success.
Keywords: Acoustic communication; Anthropogenic noise; Calling activity; Chorus; Fish; Mate choice; Reproductive success